(untitled) (Journal of Innovation and Technology Polbeng Series on Informatics (INOVTEK Polbeng - Seri Informatika), 2025)
This research develops a Decision Support System (DSS) that integrates the Fuzzy AHP (FAHP), VIKOR, TOPSIS, and GIS methods to optimize the prioritization of the realization of Work Request (SPK) documents for the house holds gas network project in Tangerang City. FAHP is used to determine the weights of five main criteria, namely: workforce readiness (28%), material availability (22%), location accecibility (20%), customer urgency (18%), and permit status (12%). VIKOR and TOPSIS are used for ranking the alternative SPK, while GIS is used for spatial analysis and visualization. Testing (UAT) involving 10 end-users using a Likert Scale questionnaire and the System Usability Scale (SUS). The evaluation result show an SUS score of 82 (categorized as “excellent”) and a reduction in decision-making time from an average of 2 weeks to 2 days. The FAHP weighting results also demonstrated valid consistency (CR = 0.09). This system is proven to provide a comprehensive solution in supporting energy infrastructure project priority decisions by simultaneously considering technical, administrative, and geographical aspects.